PENDAMPINGAN UJI KOMPETENSI OTOMATISASI TATA KELOLA PERKANTORAN DI SMK MUHAMMADIYAH PONTANG - Kusumawati, Nugrahini; Ende, Ende; Wijaya Kusuma, Jaka; Hamidah, Hamidah; Nursoleh, Nursoleh; Komarudin, Mamay; Widodo, Wahyu (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the graduation standards for vocational high school students is implementing a competency test of expertise (UKK). The competency test of expertise aims to find out the level of competence of students, namely competent or incompetent. This skill competency test was followed by students and students of class XII majoring in Office Governance Automation, 17 people. UKK implementation during the Covid-19 pandemic was carried out offline for one day on Sunday, March 20, 2022. The method used in Abdimas activities is as an external examiner, an assessor to provide an assessment of UKK results that students of SMK Muhammadiyah Pontang have done. The results of the UKK implementation showed that 15 students had competent criteria with a score range of 80-90, and 2 students had fairly competent criteria with a score range of 70-79. The conclusion is that the competency criteria of prospective graduates of SMK Muhammadiyah Pontang have met the minimum requirements of competencies that the government has determined